P113 Determining Thrombosis Rates in Hospitalized Patients With Inflammatory Bowel Disease. (December 2019) - Ho, Andrew; Zhou, Wendy
Abstract : BACKGROUND: While it is known that inflammatory bowel disease patients have an increased risk (3-4 fold more than the general population) of venous thromboembolisms (VTE), the rate of VTE pharmacologic prophylaxis in hospitalized IBD patients remains low despite current guidelines and recommendations. Although there are several studies that have reported a decreased incidence of VTE during hospitalization while on anticoagulation therapy, there still remains multiple barriers that prevent the administration of DVT prophylaxis during hospitalization. This includes lack of awareness in guideline-recommended use of pharmacologic prophylaxis and concerns regarding the safety of anticoagulant drugs in patients with active IBD flares. This study aims to look at VTE pharmacologic prophylaxis rates in hospitalized IBD patients and assess for independent risk factors that may prevent administration of VTE pharmacologic prophylaxis. METHODS: The study is a retrospective cohort study of adult IBD patients aged 18 years or older admitted to Santa Clara Valley Medical Center (SCVMC) for an IBD flare from 2014 – 2018. Data collected include demographics: patient age, medical history, gender, IBD type, BMI, and duration of hospital stay. Lab results of CBC, ESR, CRP, and calprotectin were also collected. Medications given during hospital stay including steroids and biologic therapy were studied. Any colonoscopy or surgery performed during hospital stay was documented. The study population included IBD patients +/- DVT prophylaxis during hospitalization. The data collected was analyzed to determine the rate of DVT prophylaxis and incidence of VTE events during hospitalization in both sets of populations. The data collected were also analyzed to determine if variables such as age, presence of leukocytosis, or past medical history, played a role in patients receiving or not receiving DVT prophylaxis during hospitalization. RESULTS: A total of 105 patients were admitted to SCMVC for an IBD flare from 2014 – 2018. Of the 105 patients, 64 patients received pharmacologic prophylaxis during hospitalization, equating to 61%. 5.7% (6 patients) of the study had a VTE, of which only 1 did not receive DVT prophylaxis. The other 5 patients all received heparin as prophylaxis on admission. However, among the 5 patients, there were intervals during the hospitalization in which heparin was not administered. We looked at the individual variables such as gender, BMI, presence of other medical comorbidities that may preclude patients from receiving pharmacologic prophylaxis, and found no statistical significance. When looking at the VTE prophylaxis rates annually, we see a gradual improvement (although not optimal) in the DVT prophylaxis (2014: 60%, 2017: 62.5%, and 2018: 72.7%). CONCLUSIONS: Our study shows that DVT prophylaxis rates in patients admitted for IBD flares are not optimal, with an average percentage of only 60%. It is possible there may be independent variables among IBD patients that may prevent administration of DVT prophylaxis, that was otherwise limited for us to determine in our small population size. Further research, and likely with a larger population size of patients admitted for IBD flares is needed to determine why DVT prophylaxis rates in IBD patients remains suboptimal.